Uncontrolled Blood Pressure in Hypertension Patients in Semarang City - Sari, Emi Yela Utami; Cahyati, Widya Hary; Ningrum, Dina Nur Anggraini (Public Health Perspective Journal, 2024)
Hypertension is blood pressure above the normal threshold of 120/80 mmHg. Uncontrolled blood pressure is blood pressure >140/90 mmHg. The purpose of this study was to analyze factors related to uncontrolled blood pressure. Controlled in Hypertension Patients in Semarang City. This study used a cross-sectional method, the research sample was 400 people with convenience sampling technique. Data collection techniques using questionnaires and medical records. Data analysis was carried out using the chi-square test and logistic regression. The results showed that there was a significant relationship between the variables of age p value 0.043 <0.05; PR1.141, drug consumption compliance 0.027 <0.05; PR 0.864, obesity incidence p value 0.023 <0.05; PR1.157 , education level p value 0.020 <0.05; PR1,190, smoking status p value 0.017<0.05; PR1,271, exercise habits p value 0.012<0.05; PR1,186, stress events p value 0.036<0.05; PR1,146, marital status p value 0.39<0.05; PR0,865, and there is no relationship between gender p value 0.151>0.05 , with uncontrolled blood pressure in hypertensive patients in Semarang City. The obesity variable (p value 0.023<0.05) is the most risky variable or the most related to uncontrolled blood pressure in hypertensive patients in Semarang City. The conclusion of the results of this study is that there is a relationship between age, drug compliance, obesity events, education level, smoking status, exercise habits, stress events and marital status with uncontrolled blood pressure in hypertensive patients in Semarang City.